Pengaruh discretionary accrual terhadap earnings management: Studi pada perusahaan otomotif yang terdaftar di bursa efek indonesia periode 2012 – 2016 - Ersi Sisdianto; Rahmat Fajar Ramdani; Ainul Fitri (Penerbit Goodwood, 2019)
Purpose: This study aims to provide an overview of the effect of discretionary accruals on earnings management. Research methodology: The research uses quantitative methods that take secondary data from annual financial statements. Results: The results show that discretionary accruals have a positive and significant effect on earnings management in the automotive and component sector manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. Limitation: This study only discusses how much influence of discretionary accruals on earnings management. Also, the number of samples and populations are less than 100 samples. Thus, it is possible for further research to conduct similar research with more samples. Contribution: This research provides new literature related to the effect of discretionary accruals on earnings management. Keywords: Discretionary accrual, Non discretionary accrual earnings management, Profit reporting